Hedging strategy against exchange rate volatility in Indonesian export-import companies : a case study on PT Astra International, Tbk - Muhammad Bahanan; Prisilia Angel Tantri; Fitriya Andriyani; Rezha Isyraqi Qastalano (Sean Institute, 2025)
This study aims to explore and evaluate the hedging strategies employed by PT Astra International Tbk in managing exchange rate volatility resulting from its export-import activities. Using a qualitative approach with a case study method, the research utilizes secondary data from financial statements, annual reports, and official disclosures from 2020 to 2024. The findings reveal that Astra consistently applies both financial hedging using instruments such as forward contracts and cross-currency swaps and natural hedging through currency alignment in operational flows. Despite occasional accounting losses from derivative instruments, the company demonstrates high hedging effectiveness, averaging over 98% in reducing potential exchange rate losses. This study contributes to the understanding of risk management practices in emerging market corporations and underscores the importance of integrating derivative instruments into corporate treasury systems. The results offer practical insights for companies facing foreign exchange risk and support theoretical frameworks on financial risk mitigation and corporate governance.